2005
DOI: 10.1002/jor.20027
|View full text |Cite
|
Sign up to set email alerts
|

Causes of mechanically induced collagen damage in articular cartilage

Abstract: Osteoarthritis (OA) is a multifactorial disease, associated with articular cartilage degeneration and eventually joint destruction. The phases of the disease have been described in detail, and mechanical factors play an important role in the initiation of OA, but many questions remain about its etiology. Swelling of cartilage, one of the earliest signs of damage, is proportional to the amount of collagen damage. This strongly suggests that damage to the collagen network is an early event in cartilage degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 45 publications
(47 reference statements)
7
126
1
1
Order By: Relevance
“…38 Excessive shear strain causes abundant collagen fibril strain that has been shown to correspond accurately with areas of collagen destruction leading to cartilage damage. 39 Our results showed that the tibial plafond exhibited 70% higher shear moduli in comparison with the talar dome. This study showed an important disparity in the ability of the tibial plafond and talus to withstand tensile, compressive, and shear forces, indicating the presence of a complex pathogenic mechanism responsible for cartilage degeneration.…”
Section: Disparity In Articulating Surfaces Of Anklementioning
confidence: 51%
“…38 Excessive shear strain causes abundant collagen fibril strain that has been shown to correspond accurately with areas of collagen destruction leading to cartilage damage. 39 Our results showed that the tibial plafond exhibited 70% higher shear moduli in comparison with the talar dome. This study showed an important disparity in the ability of the tibial plafond and talus to withstand tensile, compressive, and shear forces, indicating the presence of a complex pathogenic mechanism responsible for cartilage degeneration.…”
Section: Disparity In Articulating Surfaces Of Anklementioning
confidence: 51%
“…These studies, however, have generally investigated only the path of tibial contact and have ignored the complex rolling and sliding components of the articular surface interaction. Given that articular cartilage is more susceptible to damage from shear than from compressive forces [38], the direction and magnitude of stress applied at the area of joint contact may be even more important than its location. The joint sliding distance, calculated from the femoral and tibial joint contact path lengths, reflects shear motion and is therefore related to shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, shear stress has been documented with in vitro studies as a negative factor in cartilage failure as a response to injury and extracellular matrix wear. 17,18 Development of a superficial zone damage model through excessive shear would highlight the role of the superficial zone in the progression from healthy cartilage to PTOA. Superficial zone integrity is important for healthy cartilage function, as it provides resistance to shear forces due to the orientation of the collagen fibers.…”
Section: Introductionmentioning
confidence: 99%